1996
DOI: 10.1523/jneurosci.16-18-05715.1996
|View full text |Cite
|
Sign up to set email alerts
|

Laser Ablation ofDrosophilaEmbryonic Motoneurons Causes Ectopic Innervation of Target Muscle Fibers

Abstract: We have tested the effects of neuromuscular denervation in Drosophila by laser-ablating the RP motoneurons in intact embryos before synaptogenesis. We examined the consequences of this ablation on local synaptic connectivity in both 1st and 3rd instar larvae. We find that the partial or complete loss of native innervation correlates with the appearance of alternate inputs from neighboring motor endings and axons. These collateral inputs are found at ectopic sites on the denervated target muscle fibers. The for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 70 publications
1
32
0
Order By: Relevance
“…Staining of 3 rd -instar larval synapses with anti-CSP also revealed that the placement of motoneuron terminals on abdominal wall muscles is normal in sax and Mad mutants (data not shown). When muscles are innervated ectopically by incorrect motoneurons the placement of the synapses is abnormal (Chang et al, 1996). These studies of embryos and 3 rd -instar larvae suggest that correct innervation of muscles 6 and 7 by the RP3 motoneuron is achieved in sax and Mad mutants.…”
Section: Mad and Sax Mutants Have Impaired Nmj Morphology And Functionmentioning
confidence: 76%
“…Staining of 3 rd -instar larval synapses with anti-CSP also revealed that the placement of motoneuron terminals on abdominal wall muscles is normal in sax and Mad mutants (data not shown). When muscles are innervated ectopically by incorrect motoneurons the placement of the synapses is abnormal (Chang et al, 1996). These studies of embryos and 3 rd -instar larvae suggest that correct innervation of muscles 6 and 7 by the RP3 motoneuron is achieved in sax and Mad mutants.…”
Section: Mad and Sax Mutants Have Impaired Nmj Morphology And Functionmentioning
confidence: 76%
“…For example, the stereotypic neuromuscular connections in Drosophila larvae are able to reorganize after the ablation of a specific motoneuron during development. The corresponding target muscle can receive synaptic input from neighboring motoneurons as a result of axonal sprouting of neighboring motor neurons (Chang and Keshishian, 1996). Likewise in the Drosophila visual system, photoreceptor axons can sprout into neighboring empty space created by a cell fate transformation (Ashley and Katz, 1994).…”
Section: Stability Of the Olfactory Circuitmentioning
confidence: 99%
“…Laser beams have the advantage of high spatial and temporal precision (Shah and Jay, 1993), and are frequently used for selective cell elimination. In recent years, laser beams have been used to kill specific cells in Caenorhabditis elegans, Drosophila, amphibians, grasshoppers, and zebra fish to investigate cell function, cell regeneration, and cell-cell interactions (Bargmann and Avery, 1995;Chang and Keshishian, 1996;Balak et al, 1990;Kuwada, 1993;Shah and Jay, 1993). Laser beams have even been used to damage specific dyelabeled cellular components without destroying the cell (Jay and Keshishian, 1990).…”
Section: Introductionmentioning
confidence: 99%